Réponses

2014-05-19T00:58:36+02:00
A.  2 ( x + 3 ) = 3 ( x + 2 )
     2x + 6 = 3x + 6
     2x + 6 - 3x = 6
     -x = 6 - 6 
     x = 0

b.  3 ( 5 - 2x) = 2 (x - 1)
     15 - 6x = 2x -2
     15 = 2x -2 + 6x
     15 + 2 = 8x
      17 = 8x
       x = 17/8

c. 
3+2 (x -1) = 3x + 6
     3 + 2x -2 = 3x+6
      2x + 1 = 3x +6
      -6 +1 = 3x -2x
      -5 = x
      x = -5

d. 
5x - 2 (3x +1) = 3 (x - 7)
    5x - 6x - 2 = 3x -21
    -1x -2 = 3x -21
    -2 = 3x-21 + 1x
    -2 +21 = 4x
     19 = 4x
      x = 19/4
      x= 4.75